Pemodelan Non-uniform Coded-Modulation pada Kanal Akustik Bawah Air di Lingkungan Perairan Dangkal - Sholihah Ayu Wulandari; Tri Budi Santoso; I Gede Puja Astawa; Muhamad Milchan (INOVTEK POLBENG, 2019)
In this paper, presented an OFDM performance evaluation with the Non-uniform Coded-Modulation in the underwater acoustic channel in shallow water. A row of binary information is encoded by BCH code (7.4) for error correction and combined with Non-uniform modulation which is the result of modification of the subcarrier arrangement of the OFDM standard IEEE 802.11a. Modeling uses 52 subcarriers consisting of 4 pilots and 48 subcarrier data which are divided into three parts, i.e.: 24 subcarrier data with 16-Quadrature Amplitude Modulation (16-QAM) modulation, 12 subcarrier data with Quadrature phase-shift keying (QPSK) modulation and 12 other data subcarriers with Binary key-shift keying (BPSK) modulation. The channel type used describes the Additive White Gaussian Noise (AWGN) condition and is the result of measurement data. The analysis is done in terms of Signal-to-Noise-Ratio (SNR) and Bit Error Rate (BER) show that the value of the error rate of 0.001, modulation of BPSK, QPSK, 16-QAM, and Non-uniform modulation required the power each 5 dB, 8.5 dB, 10.3 dB, and 7.9 dB. However, the proposed system is able to suppress the required power up to 6 dB. The proposed system also shows better performance than fixed modulation and Non-uniform Modulation, which in this case with low power to achieve the same error rate. In addition, the proposed system has a coding gain of 1.9 dB compared to a non-uniform modulation system. Real testing is also done with measurement data at Mangrove estuary, Surabaya. The results show performance similar to simulations performed on Gaussian noise channels.